AskQ logo

STUCK ON HOMEWORK?

ASK FOR HELP FROM OUR KIASUPARENTS.COM COMMUNITY!

Question

Answer

-[-(2x-3) + 3(2-5x)]= 10 – 2x

-( -2x + 3 + 6 – 15x ) = 10 – 2x

17x – 9 = 10 – 2x

19x = 19

x  = 1

1 Reply 1 Like ✔Accepted Answer

Thank you 😊 🙏

0 Replies 0 Likes

-[(-2x-3)+3(2-5x)]=10-2x

-(-2x – 3 + 6 – 15x ) =10-2x

17x -3 = 10 – 2x

19x = 13

x = 13/19

 

Is there a bracket missing in the question?

2 Replies 1 Like

Oops. My bad. Yup, missed out. Question below. 

 

-[-(2x-3) + 3(2-5x)]= 10 – 2x

Answer : x = 1

1 Reply 0 Likes

-[-(2x-3) + 3(2-5x)]= 10 – 2x

-( -2x + 3 + 6 – 15x ) = 10 – 2x

17x – 9 = 10 – 2x

19x = 19

x  = 1

1 Reply 1 Like ✔Accepted Answer

Thank you 😊 🙏

0 Replies 0 Likes

I think your assumption of where the missing bracket is, is correct.

0 Replies 1 Like